Comparative analysis of the performance of Olympic Games-2024 finalists in wrestling - Latyshev, S. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to perform a comparative study of the performance traits of male and female wrestlers in the disciplines of freestyle and Greco-Roman wrestling at the Olympic Games in Paris in 2024.